El debate por los esclavos en las asambleas cristianas a fines del siglo II - Spléndido, Mariano (2010)
El objetivo de este trabajo es presentar la percepción cristiana de la esclavitud en la segunda mitad del siglo II desde el debate instaurado entre apologistas cristianos y escritores paganos sobre el rol de los esclavos en la extensión del culto cristiano. Dicho debate tiene como trasfondo las fuertes transformaciones que estaban sufriendo las comunidades cristianas en busca de una identidad frente al imperio. Los paganos identificaban al cristianismo como un culto promovido por esclavos. Los líderes de las iglesias trataron de promocionar la imagen opuesta: la conversión y el proselitismo proveniente de los amos, no de los esclavos.
The aim of this work is to present the Christian perception of slavery in the second half of the second Century from the discussion established between the Christian apologists and the pagan writers about the role of slaves in the spread of Christian religion. The background of the discussion reveals the strong transformations that the Christian communities were undergoing in their search for an identity in the empire. The pagans identified Christianity as a religion promoted by slaves. The leaders of the churches, on the other hand, tried to promote the opposite image: conversion and proselytism was carried out by the masters, not by the slaves.
Keywords: Cristianismo; Esclavitud; Conversión; Siglo II; Apologistas; Christianity; Slavery; Conversion; Second Century; Apologists